The Role of School Culture in Forming the Prophetic Character of Elementary School Students - Ayu, Dinda Puspita; Prayitno, Harun Joko (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
Prophetic character is a behavior that reflects the characteristics of the prophet, namely shidiq, trustworthy, tabligh, and fathanah. Prophetic character needs to be instilled in elementary schools to reduce cases of moral degradation. In instilling prophetic character, one way is through school culture. School culture is a habit in a school that characterizes and determines quality. The objectives of this study are: (1) to describe the role of school culture school culture in instilling prophetic character in Muhammadiyah Nurul 'Ilmi Elementary School; (2) to analyze the obstacles in instilling prophetic character.This study uses a qualitative method with a descriptively. This study was conducted at Muhammadiyah Nurul Ilmi' Elementary School which is located in Minggiran, Kalitengah, Karangdowo District, Klaten Regency, Central Java with informans numbering 26 including principal, teachers, and 5th grade students. Data collection techniques were interviews, observations, documentation, and questionnaires. Data analysis used the Saldana model with open coding techniques followed by thematic analysis to categorize data and data triangulation to ensure validity and reliability. The results of this study indicate that the school culture of Muhammadiyah Nurul Ilmi' Elementary School has an important role in instilling prophetic character. The existing school culture is dhuha prayer, dhuhur prayer, charity, murojaah, tahfidz, lining up before entering class, arranging shoes, and greeting. There are several obstacles in instilling prophetic character, namely children like to play, are lazy to pray, are in a bad mood, are crowded, and rarely memorize surahs. The existence of habituation activities makes students accustomed to practicing prophetic character every day.